A comprehensive survey of modern symmetric cryptographic solutions for resource constrained environments. (March 2015) - Kong, Jia Hao; Ang, Li-Minn; Seng, Kah Phooi
Abstract: Modern cryptographic algorithms play an irreplaceable role in data communication systems for various areas of applications. These algorithms are the backbone of data protection and secrecy for highly sensitive and classified data. The selection of a suitable crypto-algorithm will dynamically affect the lifespan and performance of a device in terms of battery-life, hardware memory, computation latency and communication bandwidth. In the current developments of the resource constrained environments, the trend is shifting towards lightweight algorithmic hardware designs. To select a suitable cryptographic algorithm for an application or an environment, the understandings of both the algorithmic requirements in terms of hardware and the specifications of the development platform intended has to be established. However, there are numerous ciphers in the literature that has various functionality, specifications and strength. Moreover, there are numerous literatures that cover the trend and specifications of security solutions in hardware constrained environment, employing known cryptographic algorithms. In this paper, we present a comprehensive survey of modern symmetric cryptographic solutions used in resource constrained environment (RCE), including literatures from the area of wireless sensor network (WSN), radio frequency identification (RFID), wireless identification and sensing platform (WISP) and other resource constrained platforms. This paper aims to provide a survey of the ciphers that were used in the past, and what are the ciphers that are currently active, and their respective specifications and applications in the area of modern world RCEs. On top of that, descriptive summaries of (a total of 100 symmetric ciphers) modern block ciphers (38), involution ciphers (6), lightweight block ciphers (28) and stream ciphers (28) are included and discussed, and an overview of the current contributions of various literatures, comparison and analysis of modern ciphers from the hardware and software perspective are also discussed.